A political discourse analysis of the state-of-the-nation addresses of five Philippine presidents - Jibrin, Corazon C. (Animo Repository, 2003)
This doctoral dissertation analyzes political discourse, specifically the first two State-of-the-Nation Addresses of five Philippine Presidents, namely, Ferdinand E. Marcos (SONAs 1966 and 1967), Corazon C. Aquino (SONAs 1987 and 1988), Fidel V. Ramos (SONAs 1992 and 1993), Joseph E. Estrada (SONAs 1998 and 1999), and Gloria M. Arroyo (SONAs 2001 and 2002). Copies of these SONAs were taken from the Batasang Pambansa. The framework used is Political Discourse Analysis because the study seeks to discover the exercise of power in the SONA through a management of the mind, in Van Dijk's terms. This management of the mind is hypothesized to be accomplished through the use of language that is strategically formulated to enact the functions of coercion, dissimulation, legitimization and delegitimization. Coercion is the exercise of control, which is not necessarily physical dissimulation is the control of information legitimization is the establishment of the right to be obeyed delegitimization is the presentation of one's opponent in a discrediting manner. The study reveals that the SONA can be characterized as a macro-structure that can be divided into four components, following Monroe's Motivated Sequence which is the structure followed in the production of persuasive speeches. These components are: Drawing Attention, Presenting Evidence, Proposing Action, and Urging Belief/Taking Action. There are linguistic features that realize this macro-structure, the most predominant being the transitive constructions, active voice, in order to clearly establish the feature of Agency. Metaphors are also used to reveal the SONA speaker's conceptualization of reality. The pronominals I and We are used to create a positioning effect for the participants in the discourse. Speech acts also realize the macro-structure of the SONA, and the ones used are: representatives (utterances used to present simple statements), directives (utterances used to get the hearer to do something), and commissives (utterances that commit the hearer to doing something). Likewise, the socio-political context obtaining for the SONA shapes the linguistic choices of the SONA producers. The study reveals that indeed the SONA reproduces the power of the SONA speaker through the manufacture of consent using linguistic strategies, whether the SONA speaker is aware of this or not. It is therefore recommended that a further study be made of all political discourses to determine if they also manifest this power-orientation, and if they do, how this can be minimized, if not totally eliminated.